Культурологический аспект на занятиях лингвистики в техническом ВУЗе - Шевченко, Валентина Федоровна; Полянская, Ирина Валентиновна; Полянская, В. В. (НТУ "ХПИ", 2010)
В статье рассматриваются проблемы культурологии при обучении лингвистических дисциплин в ВУЗе. Подчеркивается роль языка и культуры в процессе общения, социализации личности. Выделяется особый тип социокультурной коммуникации – вживание индивида в инокультурную среду и восприятие элементов иной культуры с целью адаптации либо интеграции.

In the article problems of culturology in learning of linguistic disciplines in higher educational university are discussed. The role of language and culture in communication process and person socialization are emphasized. A particular type of social and cultural communication – introduction an individual to another cultural environment and perception of elements of another culture with the aim of adaptation or integration is allocated.
Culturological aspect on linguistics lessons in technical higher educational university
Keywords: культурология; проблемы; процесс общения; язык; роль; социализация личности; социокультурная коммуникация; адаптация; интеграция